Light and Temperature Synchronizes Locomotor Activity in the Linden Bug, Pyrrhocoris apterus - Kaniewska, Magdalena Maria; Vaněčková, Hana; Doležel, David; Kotwica-Rolinska, Joanna (Frontiers in Physiology, 2020)
Circadian clocks are synchronized with the external environment by light and temperature. The effect of these cues on behavior is well-characterized in Drosophila, however, little is known about synchronization in non-model insect species. Therefore, we explored entrainment of locomotor activity by light and temperature in the linden bug Pyrrhocoris apterus (Heteroptera), an insect species with a strong seasonal response (reproductive diapause), which is triggered by both photoperiod and thermoperiod. Our results show that either light or temperature cycles are strong factors entraining P. apterus locomotor activity. Pyrrhocoris is able to be partially synchronized by cycles with temperature amplitude as small as 3°C and more than 50% of bugs is synchronized by 5°C steps. If conflicting zeitgebers are provided, light is the stronger signal. Linden bugs lack light-sensitive (Drosophila-like) cryptochrome. Notably, a high percentage of bugs is rhythmic even in constant light (LL) at intensity 400lux, a condition which induces 100% arrhythmicity in Drosophila. However, the rhythmicity of bugs is still reduced in LL conditions, whereas rhythmicity remains unaffected in constant dark (DD). Interestingly, a similar phenomenon is observed after temperature cycles entrainment. Bugs released to constant thermophase and DD display weak rhythmicity, whereas strong rhythmicity is observed in bugs released to constant cryophase and DD. Our study describes the daily and circadian behavior of the linden bug as a response to photoperiodic and thermoperiodic entraining cues. Although the molecular mechanism of the circadian clock entrainment in the linden bug is virtually unknown, our study contributes to the knowledge of the insect circadian clock features beyond Drosophila research.